DIAGNOSIS AND TREATMENT OF TOXOPLASMA IN HIV/AIDS PATIENTS AT VIET TIEP HOSPITAL: FROM LITERATURE TO CLINICAL PRACTICE (Vietnam Journal of Community Medicine, 2026)
Toxoplasma gondii infection is one of the common and dangerous opportunistic infections in HIV-infected patients, especially when CD4 cell counts are < 100 cells/mm³. The disease often manifests as encephalitis caused by Toxoplasma gondii, resulting in high mortality and neurological sequelae if not diagnosed and treated promptly. Diagnosis of Toxoplasma gondii infection in HIV patients remains challenging due to nonspecific clinical manifestations, limitations in specialized diagnostic tools, and overlap with other neurological conditions. This paper aims to review current literature on the diagnosis and treatment of Toxoplasmosis in HIV patients and discuss its application in clinical practice at Viet Tiep Hospital.
Keywords: Toxoplasmosis, HIV/AIDS, opportunistic infections